ANALISIS KEPUASAN PENGGUNA JARINGAN INTERNET DI PERGURUAN TINGGI SE KOTA SURAKARTA - Khoirul Huda; Dahlan Susilo; Firdhaus Hari Saputro (JURNAL GAUNG INFORMATIKA, 2013)
he analysis result in college Surakarta shows that there is 42 college in evaluasi.dikti.go.id. Base on 42 colleges which are taken for sampling with confidenceinterval 70% , it results 9 colleges. The results of analysis shows that the user is quite satisfied with distribution scale 2.18. It is resulted from the simple linear regressionmodel Y= 2.0617+0.0025x. The constant 2.0617 means bandwidth is also still constant with the value 2.0617. The satisfaction of Coefficient value to ward the internet user is0.0025. It means that there is an each increasing bandwidth of internet user 1(kbps). Therefore, it causes 0.0025 satisfaction increasing value. The conclusion of thisresearch is bandwidth capacity that less than 145 kbps categories as quite satisfied, 180-460 kbps is satisfied and more 495 kbps is very satisfied. Mikrotik and proxy aremanagement bandwidth used in college at Surakarta.